2001
DOI: 10.1677/joe.0.1700079
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal tumors of mice double transgenic for inhibin-alpha promoter-driven simian virus 40 T-antigen and herpes simplex virus thymidine kinase are sensitive to ganciclovir treatment

Abstract: We have previously produced transgenic (TG) mice expressing the mouse inhibin -subunit promoter/Simian virus 40 T-antigen (Inh /Tag) fusion gene. The mice develop gonadal somatic cell tumors at the age of 5-7 months; the ovarian tumors originate from granulosa cells, and those of the testes from Leydig cells. In the present study another TG mouse line was produced, expressing under the same inh-promoter the herpes simplex virus thymidine kinase gene (Inh /TK). Crossbreeding of the two TG mouse lines resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…occur without direct cell-cell contacts [19,20]. In contrast with the sensitivity of proliferating Leydig tumor cells for the treatment [11], the present study shows that, in single TG Inh␣/TK males, the most sensitive cells are located in seminiferous tubules. The data indicate that Leydig and Sertoli cells are highly resistant to the drug while germ cells are destroyed presumably by the bystander effect.…”
Section: Introductioncontrasting
confidence: 61%
See 1 more Smart Citation
“…occur without direct cell-cell contacts [19,20]. In contrast with the sensitivity of proliferating Leydig tumor cells for the treatment [11], the present study shows that, in single TG Inh␣/TK males, the most sensitive cells are located in seminiferous tubules. The data indicate that Leydig and Sertoli cells are highly resistant to the drug while germ cells are destroyed presumably by the bystander effect.…”
Section: Introductioncontrasting
confidence: 61%
“…Using the same promoter, we produced another transgenic (TG) mouse line expressing herpes simplex virus thymidine kinase (Inh␣/TK). By immunostaining, we showed the expression of TK both in Leydig and Sertoli cells [11]. When Inh␣/Tag mice were crossbred with Inh␣/TK mice and the double TG mice obtained were treated with ganciclovir, we were able to show the suitability of the model for testing gene therapy of gonadal tumors [11].…”
Section: Introductionmentioning
confidence: 88%
“…The cytotoxic monophosphorylated product is incorporated into elongating DNA of proliferating cells, causing chain termination and cell death . HSV-TK has already been used in experimental and clinical gene therapy trials as a conditional suicide gene to ablate tumor cells , Mikola et al 2001. We have produced another TG mouse line, expressing the HSV-TK gene under the inhα promoter and crossbred these mice with the original inhα/Tag tumor mice, to obtain double TG mice, which are susceptible to tumor ablation by treatment with antiherpes drugs (e.g.…”
Section: Future Directionsmentioning
confidence: 99%
“…We have produced another TG mouse line, expressing the HSV-TK gene under the inhα promoter and crossbred these mice with the original inhα/Tag tumor mice, to obtain double TG mice, which are susceptible to tumor ablation by treatment with antiherpes drugs (e.g. gancyclovir) (Mikola et al 2001). We have already successfully treated double TG and single TG mice of both sexes, possessing gonadal tumors, with gancyclovir, and found that the double TG tumors decreased significantly in volume during the antiherpes treatment, whereas controls inhα/Tag tumors continued growing at the same time (Mikola et al 2001 Recently it has also been found that the lytic peptide hecate, a fusion protein of a 23-amino acid and a 15-amino acid (81-95) fragment of the human CGβ chain could be used as a form of novel anticancer drug that could selectively induce the destruction of cancer cells expressing LHR.…”
Section: Future Directionsmentioning
confidence: 99%
“…Another antiviral drug, Gancyclovir, is known to induce testicular damage and germ cell apoptosis in transgenic mouse (Mikola, 2001). Both Acyclovir and Gancyclovir suppressed the gonadotropins, but that did not impinge upon the testes of treated newborn pups (Markkula et al, 1995).…”
Section: Introductionmentioning
confidence: 99%